Analysis of Indigenious Vegetation Diversity in Urban Area of Bekasi Regency - Hakim, Dani Lukman; Adji, Riyanto; Satwhikawara, Rachmi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2024)
The primary role of vegetation is to provide structural support for the surrounding ecosystem, while also contributing to the visual appeal of the road environment. The presence of Green Open Space (GOS) as a venue for sustaining the urban environment is inherently essential, owing to its substantial capacity to enhance both the qualitative and quantitative aspects of urban living. This study aimed to analyze the indigenous vegetation well-suited for developing GOS along road routes within the urban center of Bekasi Regency. The study utilizes a multi-faceted approach, including field surveys, and historical data comparison, to offer a comprehensive analysis of spatial and temporal variations in vegetation diversity. The analysis of vegetation diversity involved the quantification of canopy density, dominance frequency, important/historical value, function in landscape design, and habitat profile analysis of vertical and horizontal structures. These measurements collectively provided an assessment of the state of local vegetation that is being inventoried. The vegetation in Bekasi Regency, within both GOS and urban residential areas, generally meets satisfactory standards in supporting ecological functions. However, in specific residential locations, there remains a lack of diversity in local and rare vegetation. In summary, the study underscores the pressing demand for comprehensive conservation approaches that effectively harmonize development initiatives with the protection of indigenous biodiversity. The results of this study offer a pivotal asset for policymakers and environmental planners in crafting sustainable development strategies for Bekasi Regency.